Edge Matrices of Magnetic Sector in a Static Mass Spectrometer - Sachenko, V. D.; Antonov, A. S. (Journal of analytical chemistry (New York, N.Y.), 2023)
The first-order input and output edge transfer matrix elements of the magnetic sector in a static mass spectrometer are derived based on the conservation law of the generalized momentum of ions in a magnetic field. The structure of the edge matrix is shown to be ambiguous and dependent on the effective model, which considers the displacement of ion trajectories in the edge field. A comparison of the results obtained with traditional methods, such as expanding the edge field components and trajectory equations into asymptotic series and integrating successive approximations, reveals significant differences in the first-order edge matrix elements in the effective model of the magnetic sector, where the ideal uniform field is bounded by Herzog boundaries, compared to the published data. Algorithms for matching the input and output axes of the magnetic sector, taking into account the action of the edge fields, are given.